A bacteria-resistant and self-healing spray dressing based on lyotropic liquid crystals to treat infected post-operative wounds. Issue 38 (8th September 2021) - Yue, Xiao; Zhang, Xuejuan; Wang, Chen; Huang, Ying; Hu, Ping; Wang, Guanlin; Cui, Yingtong; Xia, Xiao; Zhou, Ziqiang; Pan, Xin; Wu, Chuanbin
Abstract : A bacteria-resistant and self-healing spray dressed designed for infected post-operative wounds. Abstract : The delayed healing of infected post-operative wounds has turned into a worldwide medical problem. In the clinical treatment, effective bacterial clearance and promoted wound healing were considered as two crucial aspects. However, the effect of current dressings with antibacterial activity was limited due to the declined efficacy against antibiotic-resistant bacteria, and poor mechanical property during skin extension and compression movement. In this project, a lyotropic liquid crystal (LLC)-based bacteria-resistant and self-healing spray dressing loaded with ε-polylysine (PLL) was designed. Owing to the unique antibacterial mechanism, PLL was expected to kill antibiotic-resistant bacteria efficiently, even the "superbug" methicillin-resistant Staphylococcus aureus ( MRSA ). The cubic cells of LLC were applied to encapsulate PLL to improve its stability and induce a sustained release, further realizing a long-term antibacterial effect. Meanwhile, the LLC precursor (LLCP) could extend to the irregular edges of the wound, and spontaneously transited to a cubic phase gel once exposed to physiological fluid. This 3D structure was also endowed with mechanically responsive viscoelasticity that formed a robust and flexible defense for wounds. An excellent antibacterial activity with more than 99% MRSA killed in 3 h was demonstrated by a killing kinetics study. The long-term effect was also proved by measuring the bacteriostatic circle test within 48 h. In addition, the unique sol–gel phase transition behavior and superior self-healing capacity of PLL-LLCP was verified with the rheological study and self-recoverable conformal deformation test in vivo . In the infected post-operative wound model, satisfactory bacterial clearance and prominent wound healing promotion were realized by PLL-LLCP, with the survival of the bacteria at lower than 0.1% and the wound closure at higher than 90%. Thus, PLL-LLCP was believed to be an excellent candidate for the therapy of infected post-operative wounds.